Continuous Spiritual Education Is A Strong Foundation For The Establishment Of A Developed Generation - Rakhmatov Olim Bakhramovich; Majitov Shokhjahon (Zien Journals, 2022)
This article discusses the role and importance of the concept of continuous spiritual education in the lives of young people, work on its implementation. , The role of priority in the draft development strategy of the new Uzbekistan in continuous spiritual education.
Keywords: Concept; competence; indicator; knowledge